How to Conduct Clinical Trials in Children: A Tutorial. Issue 3 (18th March 2019) - Shakhnovich, Valentina; Hornik, Christoph P.; Kearns, Gregory L.; Weigel, Jaylene; Abdel‐Rahman, Susan M.
Abstract : Despite a growing interest in, and commitment to, implementing pediatric clinical trials, approximately one in every five trials in children fails because of inappropriate study design, suboptimal experiment planning, or inadequate participant enrollment. This tutorial, presented from the perspectives of seasoned pediatric investigators, an experienced research coordinator, and an established pediatric clinical trials network, is designed to provide practical guidance for successfully implementing pediatric clinical trials at an academic center or another comparable institution.